Diagnosis and management of pituitary apoplexy: a Tunisian data - Faten Hadj Kacem; Oumeyma Trimeche; Imen Gargouri; Dhoha Ben Salah; Nadia Charfi; Nabila Rekik; Fatma Mnif; Mouna Mnif; Mouna Elleuch; Mohammed Abid (Chinese Neurosurgical Journal, 2023)
Abstract Background Pituitary apoplexy (PA) is defined as the hemorrhage or the infraction of a pituitary adenoma. Aiming to determine the epidemiological, clinical, paraclinical characteristics as well as management and outcomes of PA in our population, we conducted this cross-sectional study. Methods This cross-sectional study was conducted at the Department of Endocrinology of Hedi chaker university hospital, Sfax. Data was collected from medical charts of patients with pituitary apoplexy admitted in our department between 2000 and 2017. Results We included 44 patients with PA. Their mean age was 50 ± 12.6 years. Among them, 31.8% had a known pituitary adenoma, and it was in all cases a macroadenoma, predominantly a prolactin secreting tumor (42.8%). A triggering factor of PA was encountered in 31.8% of cases and it was mainly: head trauma, dopamine antagonists, and hypertension. The clinical presentation of PA encompassed headaches (84.1%), visual disturbances (75%), and neurological signs (40.9%). Gonadotropin deficiency was the most frequent form of hypopituitarism noted (59.1%), followed by corticotropin deficiency (52.3%), thyrotropin deficiency (47.7%), and somatotropin deficiency (2.3%). Hormonal assessment at PA onset, concluded that 23 had a secreting adenoma: 18 prolactinomas, 3 ACTH-secreting adenomas, and 2 GH-secreting adenomas. In the 21 remaining cases, the tumor was non-functioning (47.7%). Pituitary MRI was performed in 42 cases (95.5%), revealing infraction and or hemorrhage in the pituitary gland in 33 cases; a heterogenous signal or a fluid level within the adenoma, in nine cases. Urgent administration of intra venous hydrocortisone was required in 19 cases. Mannitol administration was mandatory in a patient who had severe intracranial hypertension. Surgical management of the PA was imperative in 24 patients (54.5%): 15 suffered from severe visual impairment, 4 had an intracranial hypertension, 2 cases demonstrated an impaired consciousness, 2 patients experienced a tumor enlargement and one case had a severe Cushing’s disease. Operative complications found were rhinorrhea attributable to cerebral spinal fluid leakage, insipidus diabetes associated with rhinorrhea, isolated insipidus diabetes, and hydrocephalus in one case each. Long-term follow-up concluded that headaches persisted in five cases, owing to the tenacity of a macroprolactinoma regardless of cabergoline treatment in one case, the recurrence of an adenoma in two cases and its persistence despite the medical and the surgical treatment in two patients. Concerning the visual acuity defects, only two patients had persistent diminished visual acuity at long-term follow-up. Among 25 patients, 13 were diagnosed with definitive thyrotropin deficiency. Similarly, 14 patients had persistent corticotropin deficiency (CD). Additionally, CD was de novo diagnosed in two patients. Otherwise, gonadotropin deficiency prevailed in all cases. Persistent prolactin deficiency was seen in two patients. Disappearance of the pituitary tumor was encountered in 11 out of 24 cases at long-term follow-up. Overall, surgery was associated with better outcome than conservative management. Pituitary apoplexy is a challenging condition due to its variable course, its diagnosis difficulty and management, as gaps remain to determine the best approach to treat this condition. Conclusions To conclude, pituitary apoplexy is a challenging condition due to its variable course, its diagnosis difficulty and management, as gaps remain to determine the best approach to treat this condition. Further studies are thus needed.